Pengembangan LKPD IPA Berbasis Value Clarification Untuk Meningkatkan Karakter Peserta Didik - Hastyarini Krisnawati; Astuti Wijayanti; Ayu Fitri Amalia (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims for knowing process developing students worksheet based on value clarification which is decent used to improve character of Junior High School grade VIII students. The study type was research and development (R&D) of 4D (Define, Design, Develop dan Disseminate) model which is restricted untill develop stage. The techniques of collecting data used observatins, questionnaires, and interviews. Quality value data obtained then analyzed used qualitative and quantitative descriptive analysis based on ideal assesment. The students worksheet meet the criteria aspects of suitability of the goal, content eligibility, completeness of the material, presentation of material, student worksheet based on value clarification components, suitability of activities, clarity of instructions, language and sentence eligibility, text clarity and layout quality. Based on expert judgment is known that worksheet student which was developed had very good quality with ideal percentage by media expert 91%, percentage assesment by material epert 87,78%, percentage assesment by peer reviewer 95,16%, percentage assesment by natural science teacher 83,03% and percentage respon by students 86,48%. Based on that assesment, student worksheet based on value clarification for Junior High School grade VIII students is suitable for use in natural science learning.